Incidence density of hyperuricemia and association between metabolism-related predisposing risk factors and serum urate in Chinese adults: a cohort study - Liang, Hailun; Zhang, Jijuan; Yu, Hancheng; Ding, Lijie; Liu, Feng; Wang, Jun (Frontiers in Endocrinology, 2023)
Abstract Background: To obtain the incidence density of hyperuricemia and to explore the association of serum urate (SU) with metabolism-related indicators in Han Chinese adults in Beijing. Methods: A total of 48,979 participants were included in the study. The partial least squares path model (PLSPM) was used to explore the relationship between SU and metabolism-related risk factors. The generalized additive model was used for smooth curve fitting, showing the sex-specific changes in SU concentration with 95% confidence interval (CI) with the increase of fasting blood glucose (FBG) concentration and age. Results: The incidence density of hyperuricemia was 78/1000 person-years. Age, sex, obesity, glucose metabolism, lipid metabolism and baseline SU had statistically significant effect on SU in the follow-up. The changes of SU level with the increase of FBG levels followed a non-liner path. Sex and age differences also had significant impact on the SU level. Conclusions: The SU concentration is affected by diverse metabolism-related risk factors like BMI, FBG, TG etc. The changes of SU level with the increase of FBG levels followed a non-linear path. It is necessary to establish cut-off values for monitoring the SU concentration for people of different sexes and ages since sex and age differences also significantly impact the SU level.